Kecemasan Dalam Berbahasa Inggris pada Pembelajar Bahasa Asing - Akhmad Kanzul Fikri (Universitas KH. A. Wahab Hasbullah, 2018)
Language learners frequently showing anxiety, feeling guilty and nervousness when learning a brand new language. Language anxiety can raise from learners’ inner feeling, their self-related cognitions, language learning barriers, variety target in learners’ and language cultures, differences in social status of the speakers and from the fear of losing self-identity. Language anxiety may also be resulted as a cause of improper command of the target language (Sparks and Ganschow; cited in Horwitz, 2001: 118). It may be eencountered due to linguistic difficulties L2/FL learners met in learning the target language. This study tried to investigate the factors behind language anxiety among the Indonesian language learners. The research findings suggested that language anxiety can appear from learners’ own sense, language learning difficulties, differences in learners and target language cultures, differences in social status of the speakers and interlocutors, and from the fear of losing self-identity. Furthermore, considering the crucial role of teachers in second or foreign language pedagogy, a need was felt to investigate the beliefs and perceptions of language teachers about learning and teaching a second or a foreign language.